2019
DOI: 10.1136/bmjopen-2019-033944
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for choosing and adhering to active surveillance for localised prostate cancer: a nationwide population-based study

Abstract: ObjectiveKnowledge about factors influencing choice of and adherence to active surveillance (AS) for prostate cancer (PC) is scarce. We aim to identify which factors most affected choosing and adhering to AS and to quantify their relative importance.Design, setting and participantsIn 2015, we sent a questionnaire to all Swedish men aged ≤70 years registered in the National Prostate Cancer Register of Sweden who were diagnosed in 2008 with low-risk PC and had undergone prostatectomy, radiotherapy or started on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…It is natural to define a proxy of the diagnostic activity using the incidence of lower risk (ie, low and intermediate risk) prostate cancer because such disease is more often asymptomatic 42,51 than higher risk disease, and because the incidence has increased threefold between 1992 and 2016, Figure S3, in line with the increase in use of PSA testing 25 . However, there are several others risk categorization systems, and some could be more predictive of prostate cancer death.…”
Section: Discussionmentioning
confidence: 99%
“…It is natural to define a proxy of the diagnostic activity using the incidence of lower risk (ie, low and intermediate risk) prostate cancer because such disease is more often asymptomatic 42,51 than higher risk disease, and because the incidence has increased threefold between 1992 and 2016, Figure S3, in line with the increase in use of PSA testing 25 . However, there are several others risk categorization systems, and some could be more predictive of prostate cancer death.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in other contexts have shown that time pressure is associated with less adherence to guidelines [14] and greater decisional regret [15]. Although lPCa often does not require immediate action, the word "cancer" alone may create a desire for rapid local treatment in many patients [16]. Given the resulting time pressure, it is a challenge to carefully discuss the respective side effects of all treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Formal AS protocols include monitoring the cancer via periodic PSA tests, digital rectal exams, prostate biopsies, and MRI. 4,5,13,[20][21][22][23] Monitoring provides the option to undergo curative treatment and is based on evidence of disease progression and on patient and physician preferences. Several studies have shown that disease progression results in switching from AS to surgery or radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that disease progression results in switching from AS to surgery or radiation. 13 , 20 , 23 , 24 Among the few studies that have conducted a longitudinal assessment of the role of patient preferences and anxiety in switching to AT, there is evidence of discontinuing AS due to anxiety or personal preference and without evidence of disease progression. 23 , 24 , 25 However, not all studies have found strong evidence showing that PCa‐related anxiety results in being more likely to opt out of AS.…”
Section: Introductionmentioning
confidence: 99%